Electric efficiency of the erector spinae in high performance amateur tennis players - Renkawitz, T.; Linhardt, O.; Grifka, J. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The aim of the paper was to evaluate neuromuscular activity patterns of the lumbar erector spinae during isometric voluntary maximum trunk extension and how this could be influenced through a back exercise home program in high performance amateur tennis players. Methods. Experimental longitudinal study of the lower back in a clinical setting. Seventy high performance amateur tennis players underwent isometric trunk extension tests in a specially built apparatus with simultaneous surface electromyography (EMG) recording from right and left lumbar erector spinae. Imbalance quotients were calculated using Electric Efficiency measures. Isometric and electromyographic changes were reviewed after a 7-week daily home program of back exercise. Results. Neuromuscular imbalance of the lumbar erector spinae associated with reduced Electric Efficiency, closely related to handedness was observed amongst tennis athletes at the start of the study. After a 7-week back exercise home program, lumbar neuromuscular imbalances were evened out and the Electric Efficiency of the erector spinae improved significantly at lumbar level L2 and L4. No significant difference was measured in maximal isometric trunk extension strength. Conclusion. The asymmetric trunk loading caused by tennis specific biomechanics with trunk hyperextension motions and trunk rotation seems to induce imbalanced muscle activity patterns of the lumbar erector spinae. A home program of back exercises for tennis players can help to compensate for these imbalances, improves Electric Efficiency patterns of the erector spinae and should therefore be integrated in the daily training routine of high performance tennis players.